Efficient fabrication of metal sulfides/graphite anode materials derived from spent lithium-ion batteries by gas sulfidation process. (September 2021) - Xiao, Z.; Gao, L.; Su, S.; Li, D.; Cao, L.; Ye, L.; Zhang, B.; Ming, L.; Ou, X.
Abstract: Although regeneration of spent lithium-ion batteries is of great significance for alleviating resource-shortage and addressing environment issues, the recycling process still confronts with great challenges. Meanwhile, majority of recycling processes concentrate on the cathode materials, while the anode material has received little attention because of its low value. In this study, we develop a novel recycling process for spent LiNix Coy Mn1-x-y O2 /LiNix Coy Al1-x-y O2 /graphite materials to prepare carbon–metal sulfides composites (NCMS/C and NCAS/C) by the gas sulfidation method. During this regeneration process, it can not only fulfill the efficient recycling within a short procedure of solid–solid transformation without involving tedious acid–base neutralization reaction, but also realize the recycling of high-valued components within the spent batteries simultaneously. Benefiting from the synergistic effect of the tight contact between metal sulfides and reconstructed graphite with high conductivity, it delivers the outstanding electrochemical properties for lithium storage (NCMS/C: 900.4 mAh g −1 at 0.2 A g −1 after 200 cycles, NCAS/C: 830.5 mAh g −1 at 0.2 A g −1 after 200 cycles). It is noted that this approach provides a new insight into the transformation from spent lithium-ion batteries to value-added materials with efficient reutilization, which makes full use of the valuable components by recycling spent cathode and anode materials synchronously, to achieve the win-win situation of environment protection and resource conservation. Graphical abstract: Image 1 Highlights: The recovery process accomplishes the simultaneous recycling of both cathode and anode materials. The direct gas sulfidation displays a short recycling process with greatly improved recovery efficiency. The regenerated carbon–metal sulfide anodes demonstrate promising performance for lithium storage.